A Case of Chorioretinitis with Retinal Angiomatous Proliferation. (26th December 2021) - Chen, Yanru; Wei, Mingyan; Chen, Qian; Li, Minghan
Abstract : A 48-year-old woman had an acute blurred vision in the right eye immediately after drainage of liver abscess. Her best corrected visual acuity (BCVA) was 8/400; fundus photography suggested the diagnosis of endogenous endophthalmitis with chorioretinitis and vitritis. Due to the bad systemic condition, a systemic antibiotic combined with periocular triamcinolone (TA) was carried out first. Inflammatory cells in the vitreous cavity were decreased after treatment; however, fundus fluorescein angiography (FFA) showed abnormal dilation and leakage of the capillaries and retinal-choroidal anastomose, supporting that there was retinal angiomatous proliferation (RAP). Vitreous interleukin-6 (IL-6) was only slightly elevated; the ratio of interleukin-10 (IL-10) and IL-6 was less than 1, and the etiological test was negative. After receiving intravitreal vancomycin injection combined with periocular TA injection, the patient's BCVA was improved from 16/400 to 20/400 with a reduction in vitreous inflammatory cells. However, the patient's RAP was progressed and her BCVA was dramatically decreased to count finger/30 cm. After intravitreal injection of ranibizumab, the patient's BCVA was 5/400 with a significant shrink in lesions and absorption of hemorrhage, exudation, and fluid. Thus, we suggest that early anti-inflammatory treatment in conjunction with anti-VEGF may achieve a better prognosis in patients with inflammatory retinal angiomatous proliferation (RAP).